Shelley’s Posthumous Ditty - Wilson, Mr. Patrick J. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This article will explore one of Percy Bysshe Shelley's posthumous poems, Shelley's "Music, When Soft Voices Die" (1824). Although some assert this verse is one of Shelley's most anthologized and powerful of the young poet's verse, I believe the verse does not entice a great deal of scholarly appreciation, perhaps, because of its length, and; possibly, because some may find the poet's topic of perseverance of memories, events, and sensations to be too ordinary. This commentary makes a thought-provoking reading of Shelley’s lyrical fragment by cherishing what some read as too ordinary a subject and viewing Shelley’s poem and subject matter as something not only realistic to all of us, but also displays how the ordinary things in one’s life are complex by our very nature and sophisticated perspective from this world to the afterlife. This paper also explores various inspirations from this particular lyric; also, it looks at the significance of when it was written and published as it relates to Shelley’s premature death, for maybe Shelley was thinking of someone besides his good friend, John Keats, when he was writing this poem.